(untitled) (Ameghiniana, 2013)
The genus Eubaculites Spath is represented, in northcentral Patagonia, by the species E. ootacodensis (Stoliczka ), which also occurs in Australia, India and California, with a dubious record frorn Madagascar. In Argentina this species occurs in levels which, on the basis of micropaleontological studies, are considered as being of Lower-Middle Maastrichtian age. "Baculites argentinicus" Weaver, 1927, a doubtful Eubaculites, is considered a nomen dubium.